2011
DOI: 10.1590/s0101-31222011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Secagem estacionária de sementes de soja com ar desumidificado por resfriamento

Abstract: RESUMO -O presente trabalho foi realizado com o objetivo de monitorar o processo de secagem de sementes de soja utilizando ar desumidificado por resfriamento. Utilizaram-se sementes de soja, cultivar Campo Mourão, secadas em secador estacionário com distribuição radial do fluxo do ar, modelo Dry-Excel, com capacidade estática para 10 toneladas e o equipamento Dry 60 ® . O processo de secagem consistiu em remover inicialmente a umidade do ar pelo resfriamento a temperatura abaixo do ponto de orvalho e posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Avelar et al (2011) state that the maximum temperature for the safe drying of seeds is dependent on the species, but generally ranges between 35 and 45 °C, and for partially dry seeds this temperature may be higher. Barbedo and MarcosFilho (1998) have subjected Caesalpinia echinata (common names include Brazilwood, Pau-Brasil, Pau de Pernambuco, Pernambuco tree, Nicaragua wood and Ibirapitanga (Tupi)) seeds to drying in greenhouses regulated at 40 and 50 °C, reducing the water content up to 8%, and have found no drying temperature effect on seed germination.…”
Section: Resultsmentioning
confidence: 99%
“…Avelar et al (2011) state that the maximum temperature for the safe drying of seeds is dependent on the species, but generally ranges between 35 and 45 °C, and for partially dry seeds this temperature may be higher. Barbedo and MarcosFilho (1998) have subjected Caesalpinia echinata (common names include Brazilwood, Pau-Brasil, Pau de Pernambuco, Pernambuco tree, Nicaragua wood and Ibirapitanga (Tupi)) seeds to drying in greenhouses regulated at 40 and 50 °C, reducing the water content up to 8%, and have found no drying temperature effect on seed germination.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors such as Krzyzanowski et al, (2006a); Krzyzanowski et al, (2006b); Levien et al, (2008); and Avelar et al, (2011), have already tested the heat pipe technology (HPT) and proved its efficiency in drying grains. In coffee, this drying method also showed results that corroborate our findings on the maintenance of grain quality.…”
Section: Number Of Defective Grainsmentioning
confidence: 99%
“…With the advances in drying air dehumidification (e.g., heat pipe technology -HPT), electricity became part of the drying process in a financially competitive scenario. In Brazil, HPT was firstly applied in peanut drying by Krzyzanowski et al, (2006a), as well as in soybean by Krzyzanowski et al, (2006b); Levien et al, (2008); and Avelar et al, (2011). These authors used dehumidified air to dry seeds and found a reduction in drying time and greater maintenance of seed physiological quality.…”
Section: Introductionmentioning
confidence: 99%
“…With the dehumidification of air resulting in greater potential for withdrawal of water from the seeds, this technique can accelerate the drying process, correlating with an energy savings. Avelar, Levien, Peske, Villela, and Baudet (2011) analysed the efficiency of stationary drying of soybean seeds with an apparatus similar to that used in this study and found it possible to dry soybean seeds on a commercial scale.…”
Section: Asmentioning
confidence: 99%